Pendidikan Karakter: Konsep dan Aktualisasinya dalam Sistem Pendidikan Islam - Mudlofir, Ali (Nadwa, 2013)
Islam highly emphasizes character that becomes the substance of the religi-on. The character used as the basis of the education system in Islam. Cha-racter education is an attempt to make influence the soul of the students to inculcate morals, to shape the human personality and virtuous in accordan-ce with the teachings of Islam. Character education becomes essential for life. Characters are formed by at least covers: religious, honest, tolerant, disciplined, hard-working, creative, independent spirit of nationalism, pa-triotism, recognize excellence, friendship/communicative, love peace, love reading, environmental care, social care and responsibility. These values are a form of social piety which must be actualized in the education system so that they can ward off the crisis and stem the multidimensional towards the formation of personal morality. The characters must be actualized in the education system so as to form a virtuous man.